2022
DOI: 10.1111/ggi.14465
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of the COVID‐19 pandemic on facility‐ and home‐dwelling people with dementia: Perspectives from professionals involved in dementia care

Abstract: The present study aimed to investigate the impact of the coronavirus disease 2019 (COVID-19) pandemic on facility-and home-dwelling people with dementia (PWD).Methods: This observational study included two anonymous online survey questionnaires to explore the impact of the first wave of the COVID-19 pandemic in Japan and the long-term impact during the 2 years from the onset of the pandemic. The participants were medical and long-term care facilities representatives for older people (945 facilities in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Studies that reported the highest percent proportions were from Portugal ( Borges-Machado et al, 2020 ), Italy ( Carlos et al, 2021 ), and Spain ( Barguilla et al, 2020 ), due to limited social activities. Another study from Japan ( Kazawa et al, 2022 ) reported ones of the highest proportions from both groups who resided in private and residential care facilities, possibly due to more prolonged isolation than other studies until the second period of July-December 2021. Of the 10 studies, data from seven studies were collected by structured telephone interviews, while two used paper-based surveys and one used online survey.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Studies that reported the highest percent proportions were from Portugal ( Borges-Machado et al, 2020 ), Italy ( Carlos et al, 2021 ), and Spain ( Barguilla et al, 2020 ), due to limited social activities. Another study from Japan ( Kazawa et al, 2022 ) reported ones of the highest proportions from both groups who resided in private and residential care facilities, possibly due to more prolonged isolation than other studies until the second period of July-December 2021. Of the 10 studies, data from seven studies were collected by structured telephone interviews, while two used paper-based surveys and one used online survey.…”
Section: Resultsmentioning
confidence: 80%
“…Included studies that addressed the highest percent proportions were from Greece ( Tsapanou et al, 2021 ), and Italy ( Cagnin et al, 2020 , Manini et al, 2021 ), due to limited social activities, and Austria ( Wurm et al, 2022 ), due to limited physical activity. Postponements of clinical appointments ( Gedde et al, 2022 ), and change of overall lifestyle ( Kazawa et al, 2022 ) also contributed to worsening BPSD in studied populations. Of the 16 studies, nine were conducted by structured telephone interviews, six used online or paper-based surveys, and one used structured interview at a clinic.…”
Section: Resultsmentioning
confidence: 95%
“…These data reveal a surprising correlation between global antibiotic consumption and dementia and may support previous reports that link antibiotic usage to elevated risk for several neurodegenerative diseases, including AD and dementia ( 43 , 44 , 47 , 56 ). In addition to global antibiotic consumption and sex-specificity, the recent coronavirus disease 2019 (COVID-19) pandemic has increased the risk for dementia and dementia-related deaths, likely due to social isolation ( 113 ), reduced accessibility to social activities due to lockdowns and social distancing ( 114 , 115 ), and most importantly, the overuse of antibiotics ( 116 ). Moreover, it was recently estimated that COVID-19 increased the risk for AD twofold, and AD-related deaths increased by 16% ( 117 , 118 ).…”
Section: Bacterial Infections Antibiotics and Protein Conformational ...mentioning
confidence: 99%
“…Therefore, many studies have examined the safety and the influence of COVID-19 vaccines on the disease activity of autoimmune inflammatory rheumatic diseases. [5][6][7] However, no previous report has focused on older patients, and some of these studies did not evaluate "disease flare" based on objective parameters. In the present study, we aimed to evaluate the types and frequencies of adverse events (AEs) as a primary end-point in older patients with RA, and show the influence of COVID-19 vaccination on disease activities based on objective parameters as a second end-point.…”
Section: Geriatric Care Facilities' Concerns Regarding Hospital Admis...mentioning
confidence: 99%
“…Therefore, an online self‐administered questionnaire of medical and long‐term care facilities for older people throughout Japan was conducted to investigate the impact of COVID‐19 on PWD conditions and lives from October to December 2021 by Hiroshima University and the Japan Geriatrics Society. 6 The participants were the representatives of facilities.…”
Section: Tablementioning
confidence: 99%